2019
DOI: 10.1155/2019/2183720
|View full text |Cite
|
Sign up to set email alerts
|

Study of rs12532, rs8670 Polymorphism of Msh Homeobox 1 (MSX1), rs61754301, rs4904155 Polymorphism of Paired Box Gene 9 (PAX9), and rs2240308 Polymorphism of Axis Inhibitor Protein 2 (AXIN2) Genes in Nonsyndromic Hypodontia

Abstract: The etiology of hypodontia is complex, in which both genetic and environmental factors can be related. The main objective of our study was to contribute to elucidating the genetic background of nonsyndromic hypodontia (NSH). In this order, we selected 97 NSH subjects (70 females and 27 males) from patients referred to orthodontic treatment, and we matched to each NSH subject a control by age and sex. DNA was obtained from epithelial cells from the oral mucosa. Genotyping of the PAX9 (rs4904155 and rs61754301),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…According to the latest published data, our study is the first one who analyzed the AXIN2 rs2240308 variant on CHDs patients. Previous studies evaluated the mentioned variant on patients with hypodontia and demonstrated that the presence of a variant allele was associated with frontal agenesis [29]. Also, the mentioned variant was previously associated with cancer risk, such as colorectal cancer [30], breast cancer [31], and Hirschsprung disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest published data, our study is the first one who analyzed the AXIN2 rs2240308 variant on CHDs patients. Previous studies evaluated the mentioned variant on patients with hypodontia and demonstrated that the presence of a variant allele was associated with frontal agenesis [29]. Also, the mentioned variant was previously associated with cancer risk, such as colorectal cancer [30], breast cancer [31], and Hirschsprung disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the number of missing teeth (not including third molars), tooth agenesis can be classified as hypodontia (less than 6 missing teeth), oligodontia (6 or more missing teeth), and anodontia (all teeth missing) [ 3 , 4 ]. To date, NSH has been reported to be associated with mutations in ectodysplasin-A ( EDA ), ectodysplasin-A receptor ( EDAR ), EDAR-associated death domain ( EDARADD ), wnt family member 10A ( WNT10A ), wnt family member 10B ( WNT10B ), paired box 9 ( PAX9 ), msh homeobox 1 ( MSX1 ), axis inhibition protein 2 ( AXIN2 ), and inhibitor of nuclear factor kappa B kinase regulatory subunit gamma ( IKBKG ) [ 5 7 ]. Among these, EDA mutations could cause SH, which appears as an X-linked hypohidrotic ectodermal dysplasia (XLHED) clinical feature, and they have also been linked to isolated tooth agenesis, most likely due to complete or partial disruption of the EDA signalling pathway [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the number of missing teeth (not including third molars), tooth agenesis can be classi ed as hypodontia (less than 6 missing teeth), oligodontia (6 or more than 6 missing teeth), and anodontia (all teeth missing) [4][5]. To date NSH has been reported to be associated with mutations in ectodysplasin-A (EDA), ectodysplasin-A receptor (EDAR), EDAR associated death domain (EDARADD), wnt family member 10A (WNT10A), wnt family member 10B (WNT10B), paired box 9 (PAX9), msh homeobox 1 (MSX1), axis inhibition protein 2 (AXIN2) and inhibitor of nuclear factor kappa B kinase regulatory subunit gamma (IKBKG) [6][7]. Among which, EDA mutations could cause SH, which appears as a clinical feature of X-linked hypohidrotic ectodermal dysplasia (XLHED), and also have been linked to isolated tooth agenesis, most likely due to complete or partial disruption of the EDA signaling pathway [8][9].…”
Section: Introductionmentioning
confidence: 99%